PENDIDIKAN ISLAM BERBASIS PESANTREN RELEVANSI DENGAN SISTEM PENDIDIKAN NASIONAL - Arum Noviana; Ahmad Mustafidin (As-Sulthan Journal of Education, 2025)
Islamic education based on Islamic boarding schools is the oldest educational institution in Indonesia that has a strategic role in shaping the character and knowledge of the younger generation. Along with the development of the times, Islamic boarding schools have undergone a transformation to remain relevant to the national education system. This study aims to examine the history, characteristics, and relevance of Islamic boarding schools to the national education system, as well as to examine the challenges and opportunities faced by Islamic boarding schools in the modern era. The results of the study show that Islamic boarding schools have adopted various elements of modern education, including the integration of the national curriculum, character education, and strengthening vocational and entrepreneurship education. With its flexibility and adaptability, Islamic boarding schools are able to contribute to the national education system without losing its Islamic identity. It is hoped that Islamic boarding schools will continue to develop as educational institutions that not only excel in religious learning, but also in producing competitive and globally competitive graduates.